The role of tumor stem cells and the immune microenvironment in the pathogenesis of lung cancer: mechanisms of interaction and research prospects - D. A. Kharagezov; A. A. Antonyan; E. Yu. Zlatni; A. B. Sagakyants; E. A. Mirzoyan; T. G. Ayrapetova; I. A. Leyman; A. G. Milakin; O. N. Stateshny; K. D. Iozefi; M. A. Homidov; E. A. Alekseev (Южно-Российский онкологический журнал)
Despite significant advances in the treatment of malignant neoplasms, the issue of therapy resistance mediated by cancer stem cells (CSCs) necessitates the development of new treatment strategies. Studying the role of CSCs and the immune microenvironment in the pathogenesis of cancer, particularly non-small cell lung cancer (NSCLC), is a pressing issue in modern oncology. This paper is based on an extensive analysis of recent research and aims to study the mechanisms underlying the development of NSCLC.The origin of CSCs, their markers, and the main signaling pathways involved in regulating their activity are considered. Special attention is paid to the influence of CSCs on the progression of lung cancer and the mechanisms underlying their therapy-mediated resistance. Various approaches to treating lung cancer targeting CSCs, focusing on targeted therapy aimed at specific molecular targets, are highlighted.The important role of the tumor immune microenvironment in the pathogenesis of lung cancer and its impact on CSCs is emphasized. Mechanisms of immune response regulation in tumors and the potential use of immunotherapy to improve lung cancer treatment outcomes are discussed. The article also reviews modern diagnostic and treatment methods, including molecular-genetic and immunohistochemical approaches.This paper work represents a review of current knowledge on the mechanisms of lung cancer development and is significant for understanding tumor biology and developing new treatment methods. The need for an interdisciplinary approach and comprehensive use of modern diagnostic and therapeutic methods to improve the prognosis and survival rates of NSCLC patients is emphasized. Special attention is given to the prospects of using combined therapeutic approaches, including targeted drugs and immunotherapy, aimed at suppressing CSC activity and modifying the tumor microenvironment.In conclusion, a deep understanding of the molecular mechanisms regulating CSC activity and their interaction with the tumor microenvironment opens new opportunities for developing effective treatment strategies. This review underscores the need for further research in this area to ensure more successful treatment and improved quality of life for lung cancer patients.